Hemerobiidae (neuroptera) in the midwestern region of minas gerais state, Brazil - Oliveira, Roberto C.; Lara, Rogeria I. R.; Fonseca, Alysson R.; Perioto, Nelson W. [UNESP] (Soc Colombiana Entomologia-socolen, 2013)
This study aimed to identify the Hemerobiidae (Neuroptera) associated to Brazilian savannah and gallery forest, in Minas Gerais State, Brazil. The sampling was carried every two weeks at Brazilian savannah (Cerrado) in Divinopolis and at gallery forest in Pedra do Indaia, both in Minas Gerais State, Brazil. Collecting was carried out between November 2003 and October 2004, with Malaise traps. A total of 181 specimens of five species of Hemerobiidae were collected. The species Nusalala tessellata, Megalomus impudicus, Hemerobius bolivari and Notiobiella sp. were collected in the two sites; the fifth species Sympherobius sp. was found only in Pedra do Indaia. The species of diversity (index of Shannon-Wiener) and the equitability (J) of Hemerobiidae were similar in the areas of Brazilian savannah and gallery forest (H'=0.47-0.49, respectively, and J=0.78-0.69, respectively), and the differences observed between the two locations were not significant.
Keywords: Brown lacewing; Biodiversity; Taxonomy; Neotropical